Implementasi Pembelajaran Make a Match untuk Meningkatkan Kreativitas Pembelajaran Siswa Kelas X di SMA Negeri 2 Kampar Kiri Tengah pada Mata Pelajaran Biologi dengan Pokok Bahasan Pencegahan dan Pengobatan Infeksi Virus - Rosanti, Fitria (Tematik: Jurnal Penelitian Pendidikan Dasar, 2023)
This research concentrates on enhancing learning creativity among class X students at SMA Negeri 2 Kampar Kiri Tengah. Conducted as classroom action research across two cycles, involving planning, action implementation, observation, and reflection. The study, encompassing 15 class X students, reveals the efficacy of the "make a match" learning model in elevating biology learning outcomes. Key findings include: (1) The utilization of the "make a match" model significantly amplifies student engagement, registering an 80% increase. (2) Implementation of the "make a match" model correlates with an 80% rise in the completeness of student learning outcomes in biology. These insights underscore the effectiveness of innovative teaching strategies, emphasizing the role of the "make a match" model in fostering active participation and academic achievement in the biology curriculum, thus presenting a promising avenue for advancing pedagogical approaches. In conclusion, the study suggests that the "make a match" model contributes significantly to students' active engagement and academic success in biology education, showcasing its potential as a transformative pedagogical tool.